2007
DOI: 10.1007/s10295-007-0221-9
|View full text |Cite
|
Sign up to set email alerts
|

Basis for formulating biosurfactant mixtures to achieve ultra low interfacial tension values against hydrocarbons

Abstract: Biosurfactants could potentially replace or be used in conjunction with synthetic surfactants to provide for more cost-effective subsurface remediation. The design of surfactant formulations that are effective in lowering interfacial tension (IFT), which is necessary to mobilize entrapped hydrocarbons, requires information about the surface-active agent (surfactant) and the targeted non-aqueous phase liquids (NAPL). We hypothesized that biosurfactant and synthetic surfactant mixtures can be formulated to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Furthermore, it also reported that lipopeptide biosurfactant could be produced by bacteria in an oil reservoir [9]. Nutrition supplementation could increase the in-situ production of lipopeptide biosurfactant in oil reservoirs [10].…”
Section: ■ Introductionmentioning
confidence: 95%
“…Furthermore, it also reported that lipopeptide biosurfactant could be produced by bacteria in an oil reservoir [9]. Nutrition supplementation could increase the in-situ production of lipopeptide biosurfactant in oil reservoirs [10].…”
Section: ■ Introductionmentioning
confidence: 95%
“…CMC is the concentration at which the biosurfactants form micelles and is the minimum concentration needed to mobilize entrapped oil (Youssef et al 2009;Sen 2010). Many synthetic surfactants have higher CMC (>100 mg/L) than biosurfactants (Youssef et al 2007a). Thus, low biosurfactant concentrations can be effective in mobilizing entrapped oil.…”
Section: Types Of Biosurfactantsmentioning
confidence: 99%
“…To our knowledge, there are still not any reports of ex situ field trial applications of biosurfactants. A promising approach is the use biosurfactants in conjunction with synthetic surfactants to reduce the amount of synthetic surfactants needed, providing cost savings (Youssef et al 2007a;Al-Sulaimani et al 2012).…”
Section: Injection Of Ex Situ-produced Biosurfactantsmentioning
confidence: 99%
“…It is generally believed that the main synergistic mechanism for the EOR of biosurfactants and chemical surfactants is by reducing the oil/water IFT and by altering the wettability. , Al-Wahaibi et al suggested that the mixture could improve the macroscale sweep efficiency by IFT reduction while improving the microscale washing efficiency after hot water injection by reducing the viscosity . Youssef et al found that mixtures with different biosurfactants and chemical surfactants could achieve an ultra-low IFT by changing the fatty acid composition of the biosurfactant. , Mędrzycka et al suggested that a mixture of a biosurfactant and a surfactant can reduce the critical micelle concentration (cmc), which reduces the cost of surfactant flooding…”
Section: Introductionmentioning
confidence: 99%
“…13 Youssef et al found that mixtures with different biosurfactants and chemical surfactants could achieve an ultra-low IFT by changing the fatty acid composition of the biosurfactant. 21,22 Medrzycka et al suggested that a mixture of a biosurfactant and a surfactant can reduce the critical micelle concentration (cmc), which reduces the cost of surfactant flooding. 23 With regard to the mechanism of wettability alteration, a wetting test using a synthetic base oil indicated that the wettability was more efficiently altered by a mixture of a nonionic surfactant (NS) (ROKAnol NL6) and a biosurfactant (rhamnolipid JBR 425) than by either single component.…”
Section: Introductionmentioning
confidence: 99%